Study onCarbon Dioxide in Several Types of Amines - Abdul Rahman, Aina Suharny (universiti teknologi petronas, 2004)
This project is basically to study the carbon dioxide (CO2) absorption in several types of amines. In recent years, the importance of the chemical absorption process rises as a competitive process to reduce the discharge of C02 into atmosphere. This is due to C02 characteristics as it is one of the primary green house gases which represent approximately 83% of anthropogenic effect. Besides, absorption of acid gases such as CO2 from natural and refinery gases is an important industrial process. Aqueous alkanolamines solutions are the most widely used solvents for the acid gas absorption process, Aqueous alkanolamines that are used in the study are monoethanolamine (MEA), diethanolamine (DBA) and 2-amino-2-methyl-l-propanol (AMP). The objectives of this project are to determine the amount of C02 that being absorbed in amines, to determine the changes in inlet and outlet concentration of C02 during absorption, to determine the changes in concentration of amines and finally to determine the best mix aminesfor optimum absorptionof C02. The scope of this project includes studying the C02 absorption into aqueous alkanolamines and mixed aqueous solutions of alkanolamines with varying temperature and concentration of alkanolamines by measuring the inlet and outlet of C02 concentration and concentration of amines after the absorption. This study will also involve the measurement of density of aqueous alkanolamines and its mixture. The findings are then compared to the trend obtained from previous literature. From the result obtained, it can be concluded that as concentration of aqueous amines increases, rate of absorption increases. Theoretically, for temperature effect, as temperature increases, rate of absorption decreases. However, this study does not fully obey the theory due to some conditions which will be discussed thoroughly in this paper. The addition of primary and secondary amines, MEA and DEA into sterically hindered amine, AMP results in significant enhancement of CO2 absorption rates. Amine blends ofMEA and AMP gives better C02 absorption rates compared to DEA and AMP blends as MEA being primary amines has stronger effect towards C02 absorption.